The Tragedy of Myanmar Higher Education Under the Coup - Lall, Marie (International Higher Education, 2021)
Myanmar’s military coup has interrupted a decade of reforms, including important changes to higher education. Students and staff are at the forefront of anti-coup protests, bearing the brunt of the violence. This article gives a brief overview on how the higher education sector has been affected, arguing that the Tatmadaw (the Myanmar military) has no qualms about damaging higher education, seeing the revolt of students and staff as treason to the country.